Complete Blood Test as a New Prognostic Factor in Fournier’s Gangrene - Ivan D. P. Sunardi; Ari Astram; Christof Toreh; Eko Arianto; Fredrik G. Langi (e-CliniC, 2022)
Abstract: Fournier’s gangrene is a form of necrotizing fasciitis that begins in the genital and perineal areas and can extend through the fascia to the groin, thigh, and even the abdominal wall. This disease is still associated with a high mortality rate even though with comprehensive therapy. Simple examination, such as a complete blood count, is widely used as a marker of inflammation and could be used as a prognostic factor for Fournier’s gangrene. This study aimed to compare Fournier Gangrene Severity Index (FGSI) and complete blood count as a prognostic factor in Fournier’s gangrene cases by using machine learning. This was an observational study with a longitudinal data collection design according to cohort method. The results obtained 30 patients with Fournier’s gangrene at Prof. Dr. R. D. Kandou Hospital, Manado. Mortality prediction analysis using algorithms of regularized generalized linear model (GLM) and support vector machine (SVM) showed that the AUCs were 98% and 97.5% for GLM and SVM respectively for the regularized GLM and SVM in the ROC curve analysis, with the superiority to the FGSI (p<0.001). In conclusion, the complete blood count could be used as a novel prognostic value of Fournier’s gangrene cases.Keywords: complete blood count; Fournier Gangrene Severity Index (FGSI); prognostic scoring system; Fournier’s gangrene Abstrak: Gangren Fournier adalah bentuk fasiitis nekrotikans yang dimulai di daerah genital dan perineum dan dapat meluas melalui fasia ke selangkangan, paha, dan bahkan dinding perut. Penyakit ini masih dikaitkan dengan angka kematian yang tinggi meskipun dengan terapi komprehensif. Pemeriksaan sederhana seperti hitung darah lengkap, banyak digunakan sebagai penanda peradangan dan dapat digunakan sebagai faktor prognostik untuk gangren Fournier. Penelitian ini bertujuan untuk membandingkan Fournier Gangrene Severity Index (FGSI) dengan pemeriksaan parameter hitung darah lengkap sebagai faktor prognostik pada kasus dengan gangren Fournier menggunakan machine learning. Jenis penelitian ialah observasional dengan desain pengumpulan data longitudinal menurut metode kohort. Hasil penelitian mendapatkan 30 pasien dengan gangren Fournier di RSUP Prof. Dr. R. D. Kandou Manado. Analisis prediksi mortalitas menggunakan algoritma Regularized Generalized Linear Model (GLM) dan Support Vector Machine (SVM) menunjukkan bahwa AUC masing-masing sebesar 98% dan 97,5% untuk GLM dan SVM tereguler pada analisis kurva ROC, dengan keunggulan dibandingkan FGSI (p<0,001). Simpulan penelitian ini ialah pemeriksaan darah lengkap dapat dijadikan sebagai faktor prognostik baru untuk kasus gangren Fournier.Kata kunci: hitung darah lengkap; Fournier Gangrene Severity Index (FGSI); sistem skoring prognostik; gangren Fournier